Evolution and customisation of the RegCM model for urban climate studies: Addressing multifaceted challenges and advancing climate science - Naushin Yasmin; Safi Ullah; Sami G. Al-Ghamdi (Geography and Sustainability)
The Regional Climate Model (RegCM) proves valuable for climate analysis and has been applied to a wide range of climate change aspects and other environmental issues at a regional scale. The model also demonstrated success in diverse areas of urban research, including urban heat island studies, extreme climate events analysis, assessing urban resilience, and evaluating urbanization impacts on climate and air quality. Recently, more studies have been conducted in utilizing RegCM to address climate change in cities, due to its enhanced ability over the years to capture meteorological phenomena at city scales. However, there are many challenges associated with its implementation in meso-scale research, which are attributed to various shortcomings and thus create room for further improvement in the model. This paper presents a comprehensive overview of the evolution of the RegCM over the years and its customisation across various parameters, demonstrating its versatility in urban climate studies and underscoring the model’s pivotal role in addressing multifaceted challenges in urban environments. By addressing these aspects, the paper offers valuable insights and recommendations for researchers seeking to enhance the accuracy and efficacy of urban climate simulations using the RegCM system, thereby contributing to the advancement of urban climate science and sustainability.